“Social Integration Empowerment”: Upaya Memperkuat Industrialisasi Bandeng Di Kota Semarang - Erisa Aprilia Wicaksari; Vini Wiratno Putri; Vitradesie Noekent (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Social integration is a unitary condition of living together from various socio-cultural system units, ethnic groups and communities to interact and work together. Social integration as a reflection of the quality of this relationship, if applied to business actors, will increase the value chain for their business. So that the purpose of implementing this program is to create superior milkfish products through the creation of